Density of states measurements in a-Si:H and a-Si:H/nc-Si:H multilayer structures prepared by hot wire chemical vapor deposition. (April 2017) - Yadav, Asha; Agarwal, Pratima
Abstract: In this study, the density of states (DOS) were determined in single layer hydrogenated amorphous silicon (a-Si: H) and a-Si:H/nc-Si:H (hydrogenated nanocrystalline silicon) multilayered structures, prepared by hot wire chemical vapor deposition, by measuring space-charge limited currents in sandwich geometry using ITO(Indium Tin Oxide)/a-Si:H/Ag and ITO{a‐Si:H/nc‐Si:H} n /Ag structures. Comparisons showed that the DOS of a-Si:H layer in a-Si:H/nc-Si:H multilayer structures were higher than that of single layer a-Si:H film for the same shift in Δ E f n . The higher DOS in multilayer structures may be due to the existence of interface states between the a-Si:H and nc-Si:H layers, which could also change the local electric field at the junction under the no-bias condition. These interface states were also shown to be responsible for the observed persistent photoconductivity in these a-Si:H/nc-Si:H multilayer structures.